ANALISIS PASANG SURUT DI PULAU KARAMPUANG, PROVINSI SULAWESI BARA - SUDIRMAN ADIBRATA (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2007)
Tide phenomenon is one of oceanography parameter that important to capture fisheries or marine culture. This research has been work contains 15 piantan high of sea level from tide harmonics constanta, such as type of tide, mean sea level, chart datum, and tidal range. Type of tide is mixing semidiurnal, MSL is 73,36 cm, Chart Datum -104,29 cm from MSL, and tidal range 48,14 cm.